Beiträge zur Insekten-Fauna der DDR: Verzeichnis (check list) der im Gebiet der Deutschen Demokratischen Republik bisher festgestellten Zikaden (Homoptera: Auchenorhyncha). - Schiemenz, Hans (Contributions to Entomology = Beiträge zur Entomologie, 1970)
Much has changed in the taxonomy and the nomenclature of the cicadas in the last 20 years. At this date there is neither a catalogue nor a key to the cicadas of Central Europe that reflects the present state of research. The list presented here includes all cicadas definitely determined on the territory of the DDR (455 species) according to the present state of taxonomy and nomenclature. It is based on a critical examination and evaluation of faunistic publications, several collections and files of finds.